2006
DOI: 10.1016/j.molcel.2006.01.009
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Phosphorylation Is Required for Cellular Response to Oxidative Stress

Abstract: Aside from the well-established roles of c-Myc in the regulation of cell cycle, differentiation, and apoptosis, a recent picture is beginning to emerge linking c-Myc to the regulation of metabolic pathways. Here, we define a further function for c-Myc in determining cellular redox balance, identifying glutathione (GSH) as the leading molecule mediating this process. The link between c-Myc and GSH is gamma-glutamyl-cysteine synthetase (gamma-GCS), the rate-limiting enzyme catalyzing GSH biosynthesis. Indeed, c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(189 citation statements)
references
References 38 publications
15
157
4
3
Order By: Relevance
“…Moreover, we have shown, by using a unique mouse model that, at near-physiological levels of expression in the mammary gland, the Myc T58A mutant, which lacks T58 phosphorylation and has constitutively high S62 phosphorylation, similar to the phosphorylation pattern we report here in breast cancer, is tumorigenic whereas deregulated nearphysiological levels of WT Myc is not (19). Recent reports have demonstrated that pS62 is important for Myc binding to a number of transactivated target genes important for cell proliferation, growth, and survival (34,35). Thus, increased Myc protein stability and altered T58/S62 phosphorylation are likely to play important roles in breast tumorigenesis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, we have shown, by using a unique mouse model that, at near-physiological levels of expression in the mammary gland, the Myc T58A mutant, which lacks T58 phosphorylation and has constitutively high S62 phosphorylation, similar to the phosphorylation pattern we report here in breast cancer, is tumorigenic whereas deregulated nearphysiological levels of WT Myc is not (19). Recent reports have demonstrated that pS62 is important for Myc binding to a number of transactivated target genes important for cell proliferation, growth, and survival (34,35). Thus, increased Myc protein stability and altered T58/S62 phosphorylation are likely to play important roles in breast tumorigenesis.…”
Section: Discussionsupporting
confidence: 63%
“…Besides affecting Myc protein stability, Myc phosphorylation also affects its oncogenic activity in that the high-pS62 form of Myc is more oncogenic than the form of Myc lacking pS62 (17,19), suggesting an effect of altering this phosphorylation on Myc target gene regulation. Indeed, recent studies in other laboratories and in our laboratory have demonstrated an important role for pS62 in Myc binding to target gene promoters (34,35) (Fig. S7B).…”
Section: Breast Cancer Cells Have a Switch In Axin1 Splice Variant Exmentioning
confidence: 63%
“…Thyroid hormone and cysteine deprivation induce GCLm expression (Dasgupta et al, 2007). Nrf1, Nrf2, AP-1, NFÎşB and c-Myc seem to be involved in the regulation of the promoter activity of the GCLm gene (Wild et al, 1999;Yang et al, 2005;Benassi et al, 2006). Interestingly, it has been shown that insulin was unable to change the levels of GCLm mRNA (Okouchi et al, 2006), while GCLc levels were affected by this stimulus in the same report.…”
Section: +mentioning
confidence: 73%
“…A better understanding of post-transcriptional Myc (c-Myc) regulation in cancer cells is crucial as elevated expression of the Myc protein is observed in B70% of human tumors, whereas only B20% show amplification or translocation in regions of high transcriptional activity (Nesbit et al, 1999;Arnold and Sears, 2008). Physiologic studies in normal GNPs show N-Myc expression is important for cell replication, but N-Myc protein degradation is crucial for cell-cycle exit (Kenney et al, 2004;Sjostrom et al, 2005;Benassi et al, 2006). N-Myc transcription is increased during Shh signaling, with the Cdk1 complex reported to regulate the phosphorylation of serine-62-N-Myc (S62 P -N-Myc, formerly referred to as S54-N-Myc), priming N-Myc for protein degradation (Oliver et al, 2003;Kenney et al, 2004;Sjostrom et al, 2005) before phosphorylation of threonine-58 (T58 P , formerly referred to as T50-N-Myc) by GSK-3b (Sears, 2004;Sjostrom et al, 2005).…”
Section: Introductionmentioning
confidence: 99%